2020
DOI: 10.3390/mi11111019
|View full text |Cite
|
Sign up to set email alerts
|

Current Progress towards the Integration of Thermocouple and Chipless RFID Technologies and the Sensing of a Dynamic Stimulus

Abstract: To date, no printable chipless Radio Frequency Identification (RFID) sensor-related publications in the current literature discuss the possibility of thermocouple integration, particularly for the use in extreme environments. Furthermore, the effects of a time-dependent stimulus on the scattering parameters of a chipless RFID have never been discussed in the known literature. This work includes a review of possible methods to achieve this goal and the design and characterization of a Barium Strontium Titanate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Likewise, this work does not explore the response of this tag using different various reader types or explore the response of the sensor to the effects of vibration. The effects of a dynamic stimulus have been discussed in [ 42 ] and more general response characterization from time-domain based readers can be found in [ 43 ] by Babaeian and Karmakar and by Kalansuriya et al in [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…Likewise, this work does not explore the response of this tag using different various reader types or explore the response of the sensor to the effects of vibration. The effects of a dynamic stimulus have been discussed in [ 42 ] and more general response characterization from time-domain based readers can be found in [ 43 ] by Babaeian and Karmakar and by Kalansuriya et al in [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…The low-pressure injection molding process parameters involve injection pressure of 0.06 MPa and wax melting temperature of 99 °C. To evaluate the cooling performance of the injection mold with and without CCC, a system composed of a temperature controller [12] (JCM-33A, Shinko Inc.) and a thermo-electric cooler (TEC12706AJ, Caijia Inc.) and a temperature controller (JCM-33A, Shinko Inc.), and three k-type thermocouples [13] (C071009-079, Cheng Tay Inc.) was developed. Figure 9 shows the experimental setup for investigating the cooling performance of the injection mold with and without CCC.…”
Section: Methodsmentioning
confidence: 99%
“…Existing Chipless RFID Temperature Sensor Designs Existing chipless RFID temperature sensor designs have been compared by the authors in [3] in 2018 and more recently in works such as that by Gilch et al in [34]. Attempts at thermocouple integration into chipless RFIDs have also been performed by the authors in [35], but barium strontium titanate (BST) exhibits significant ambient temperature dependencies, which dominate over the effects of the weak millivolt DC input. Under more controlled test settings, subsequent testing revealed that the device exhibits sensitivities on the order of 13 kHz/mV, which is very low and requires careful control of the ambient temperature in order for the millivolt-level sensitivity to be detected.…”
Section: Temperature Sensingmentioning
confidence: 99%